2001
DOI: 10.1038/sj.ijo.0801701
|View full text |Cite
|
Sign up to set email alerts
|

Parental influences on laboratory eating behavior in obese and non-obese children

Abstract: OBJECTIVE:To determine parental influence on obesity, eating behavior of 80 obese and normal weight children (aged 8 -12 y) was investigated in the laboratory. DESIGN: A controlled repeated measurement design was used. The mother was either present or absent while the child was eating in the laboratory. MEASUREMENTS: The eating style was measured by recording cumulative eating curves with a universal eating monitor, using yoghurt as a standardized experimental meal. RESULTS: The eating behavior of obese childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 3 publications
2
23
0
7
Order By: Relevance
“…Previous research demonstrated that children with overweight status tend to eat at faster rates compared to healthy weight children [5,6,8,9,22]. However, there has been less agreement on the differences in other microstructural patterns of eating between people with healthy weight and overweight status, with some studies finding differences [7,28,53] and other studies that did not [33,54,55]. The faster eating style was found across both overweight and healthy weight children, and many of the fast eating healthy weight children were heavier than their slower eating counterparts, though still within the healthy range.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 80%
“…Previous research demonstrated that children with overweight status tend to eat at faster rates compared to healthy weight children [5,6,8,9,22]. However, there has been less agreement on the differences in other microstructural patterns of eating between people with healthy weight and overweight status, with some studies finding differences [7,28,53] and other studies that did not [33,54,55]. The faster eating style was found across both overweight and healthy weight children, and many of the fast eating healthy weight children were heavier than their slower eating counterparts, though still within the healthy range.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 80%
“…Eine experimentelle Studie an übergewichtigen Kindern zeigte, dass die Anwesenheit der Mutter übergewichtige, nicht aber normalgewichtige Kinder zu einer höheren Bissgeschwindigkeit und -größe bei einem Testessen veranlasste, als wenn sie allein waren (Laessle, Uhl, Lindel, Muller, 2001). Mit einer erhöhten Bissgröße und einer erhöhten Nahrungsaufnahme reagieren Kinder auf steigende Portionsgrößen von Nahrung (Fisher, Rolls, Birch, 2003;Fisher, Liu, Birch, Rolls, 2007).…”
Section: Hintergrundunclassified
“…Zusätz-lich zeigt eine Betrachtung von Korrelaten von Bissgröße und -geschwindigkeit, dass die Bissgröße, unter anderem mit einem größerem elterlichen BMI und BMI-SDS des Kindes assoziiert war. Letzteres entspricht teilweise den Ergebnissen von Laessle et al (2001), denen zufolge eine höhere Bissgröße mit höherem Gewicht assoziiert war. Methodische Unterschiede könnten dazu geführt haben, dass in der vorliegenden Untersuchung kein Zusammenhang zwischen Übergewicht und einer höheren Bissgeschwindigkeit gefunden wurde: So handelte sich bei der Testmahlzeit um ein kulturübliches Abendessen, bei dem die Eltern die Möglichkeit hatten, auf das Essverhalten des Kindes Einfluss zu nehmen (Hilbert et al, 2010).…”
Section: Auswertungunclassified
See 1 more Smart Citation
“…Twenty-one feeding studies (65,(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114) were found that examined variables in school-aged children (Table 3).…”
Section: Feeding Studies In Middle Childhoodmentioning
confidence: 99%